2021
DOI: 10.1097/olq.0000000000001308
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-Platform Point-of-Care Test for Neurosyphilis Diagnosis

Abstract: Background:The diagnosis of neurosyphilis relies on cerebrospinal fluid (CSF) abnormalities (pleocytosis, elevated protein) and CSF-Venereal Disease Research Laboratory (VDRL) test. In resource-limited settings, the CSF-VDRL test may not be widely available.Methods: We optimized a commercial immunochromatographic strip test, the DPP Chembio syphilis assay, for performance with CSF and tested centrifuged CSF samples of 71 patients with syphilis (35 with neurosyphilis and 36 without neurosyphilis). A CSF dilutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A total of 1,140 full-text publications were evaluated for eligibility, 489 were deemed irrelevant to the objective, and 622 lacked sufficient data therefore they were excluded. Ultimately, our meta-analysis was limited to 29 publications ( 2 , 4 , 7 33 ) to perform the quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1,140 full-text publications were evaluated for eligibility, 489 were deemed irrelevant to the objective, and 622 lacked sufficient data therefore they were excluded. Ultimately, our meta-analysis was limited to 29 publications ( 2 , 4 , 7 33 ) to perform the quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…For diagnostic purposes, Gonzalez et al found that comparing the false-negative results of both the Treponemal test and the Nontreponemal test with the true-positive results, the false-negative results had lower CSF-VDRL titers and fewer cerebrospinal fluid white blood cells, which may be related to cerebrospinal fluid dilution ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The epidemic of syphilis and neurosyphilis in low- and middle- income countries is difficult to control due to the resource-limited settings there. However, point-of-care syphilis tests developed in recent years may relieve the pressure of disease control for its feasibility and inexpensiveness ( 56 ). JHR has also been reported in almost all types of commonly used antibiotics for syphilis, especially in the treatment of PLWH ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low-and middle-income countries also showed high prevalence rates, long diagnostic delays, low follow-up rates, and inaccessibility to trained clinicians and necessary facilities ( 54 ). Optimized commercial immunochromatographic strip tests, such as the CSF-Syphicheck and the DPP Chembio syphilis assay, showed satisfying diagnostic specificity and sensitivity compared to CSF-VDRL (62–64% sensitivity, 79–81% specificity in CSF-Syphicheck; 63–92% sensitivity, 85–100% specificity in DPP Chembio syphilis assay) ( 55 , 56 ). Though further evaluation is needed, point-of-care tests may be widely applied in resource-limited regions and contribute to the control of sexually transmitted diseases, especially for neurosyphilis and congenital syphilis.…”
Section: Diagnosismentioning
confidence: 99%
“…At present, there is no gold standard for the diagnosis of neurosyphilis, and the diagnosis depends on the comprehensive analysis of clinical manifestations, serological tests and cerebrospinal fluid tests ( 25 ). Therefore, it is urgent to find additional supportive criteria with differential significance for the diagnosis of neurosyphilis and viral encephalitis.…”
Section: Discussionmentioning
confidence: 99%